Global gene expression analysis of fission yeast mutants impaired in Ser-2 phosphorylation of the RNA pol II carboxy terminal domain. - Reza Saberianfar; Stephen Cunningham-Dunlop; Jim Karagiannis (PLoS ONE, 2011)
In Schizosaccharomyces pombe the nuclear-localized Lsk1p-Lsc1p cyclin dependent kinase complex promotes Ser-2 phosphorylation of the heptad repeats found within the RNA pol II carboxy terminal domain (CTD). Here, we first provide evidence supporting the existence of a third previously uncharacterized Ser-2 CTD kinase subunit, Lsg1p. As expected for a component of the complex, Lsg1p localizes to the nucleus, promotes Ser-2 phosphorylation of the CTD, and physically interacts with both Lsk1p and Lsc1p in vivo. Interestingly, we also demonstrate that lsg1Δ mutants--just like lsk1Δ and lsc1Δ strains--are compromised in their ability to faithfully and reliably complete cytokinesis. Next, to address whether kinase mediated alterations in CTD phosphorylation might selectively alter the expression of genes with roles in cytokinesis and/or the cytoskeleton, global gene expression profiles were analyzed. Mutants impaired in Ser-2 phosphorylation display little change with respect to the level of transcription of most genes. However, genes affecting cytokinesis--including the actin interacting protein gene, aip1--as well as genes with roles in meiosis, are included in a small subset that are differentially regulated. Significantly, genetic analysis of lsk1Δ aip1Δ double mutants is consistent with Lsk1p and Aip1p acting in a linear pathway with respect to the regulation of cytokinesis.